The Effect of Brand Image and Price on Purchasing Decisions at Samase Bandung - Zulfiqar, Ian (Journal of Economics and Business (JECOMBI), 2023)
The purpose of this research is to discover whether or not consumers at Samase Bandung take brand image and price into consideration concurrently or in part when making selections about which products to buy. Methods of quantitative research were utilized throughout the course of this investigation. The method of research that is carried out is known as field research. In this study, the methods of analysis that were applied were descriptive analysis of the respondents and variables, descriptive statistical analysis of the variables, a test of the precondition assumption, multiple linear regression analysis, and testing of the hypothesis. The findings of the study indicate that the significance value for the simultaneous test (Test F) is 0.000 < 0.05, which indicates that brand image and price concurrently have an effect that is both positive and significant on product purchasing decisions made at Samase Bandung. According to the findings of the partial test (t test), the significance value of brand image is 0.000 < 0.05, which indicates that brand image has a positive and significant effect on the decisions that customers make regarding the products that they purchase at Samase Bandung. In spite of the fact that the price significance value is 0.000 < 0.05, this indicates that the price has a favorable and significant impact on the consumer's decision to buy Samase Bandung products.